2021
DOI: 10.3390/en14102824
|View full text |Cite
|
Sign up to set email alerts
|

A Prediction Model for Battery Electric Bus Energy Consumption in Transit

Abstract: This study investigates the impacts of vehicular, operational, topological, and external parameters on the energy consumption (EC) of battery-electric buses (BEBs) in transit operation. Furthermore, the study develops a data-driven prediction model for BEB energy consumption in transit operation that considers these four parameters. A Simulink energy model is developed to estimate the EC rates and validated using the Altoona’s test real-world data. A full-factorial experiment is used to generate 907,199 scenar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 62 publications
0
14
0
Order By: Relevance
“…From Figure 5, it can be observed that the values of E sup est and E rec est , according to the proposed analysis, follow a straight line with slope according to the corresponding coefficients X 1 and X 2 in Table 5. The values E sup computed according to Equation (15), are far from the estimated values E sup est (decreasing) as the altitude decreases. This is because in the intervals where the accumulated elevation gain is less than the value X 2 •d, E sup decreases (less energy needs to be supplied since the vehicle is moving on a negative slope).…”
mentioning
confidence: 72%
See 1 more Smart Citation
“…From Figure 5, it can be observed that the values of E sup est and E rec est , according to the proposed analysis, follow a straight line with slope according to the corresponding coefficients X 1 and X 2 in Table 5. The values E sup computed according to Equation (15), are far from the estimated values E sup est (decreasing) as the altitude decreases. This is because in the intervals where the accumulated elevation gain is less than the value X 2 •d, E sup decreases (less energy needs to be supplied since the vehicle is moving on a negative slope).…”
mentioning
confidence: 72%
“…As of today, manufacturers are investing numerous technical and economic resources in the development of battery electric vehicles [13]. The commercial acceptance of hybrid technology is growing, especially in the case of cars, vans and buses used in urban areas [14][15][16], while that of long-distance trucks and coaches is beginning to emerge [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…During the optimization problem, however, the algorithm requires a huge number of iterations to update the value of e ( b , r , i ) according to the change in the operation values. In every iteration, the ADVISOR model, developed and validated by Abdelaty et al ( 24 , 25 ), is used to calculate e ( b , r , i ) for every trip. If we assume that the model needs 1,000 iterations to reach the optimal design, 247 trips (in our case study), and the simulator needs only 1 s to obtain the energy consumption rate of the trip, the solution time will take up to three days (247,000 s/60/60/24 = ∼2.86).…”
Section: Model Formulationmentioning
confidence: 99%
“…First, ADVISOR MATLAB/Simulink environment is considered an accurate tool for simulating BEB conduct ( 25 , 26 ). ADVISOR was first developed by the National Renewable Energy Laboratory (NREL).…”
mentioning
confidence: 99%
“…In this context, ATM -Azienda Trasporti Milanesi, the public company that manages the collective transport in Milan (Italy), launched in 2017 the Milan Full Electric project to equip the city by 2030 with a public transport service entirely powered by electric traction, retiring gradually the current diesel vehicles, and promoting sustainable mobility in the urban area (Wen, 2016;Wang, 2020). Several studies in the literature have addressed the issue of energy consumption by highlighting the importance of how electricity is produced (Abdelaty and Mohamed, 2021;Pietrzak and Pietrzak, 2021).…”
Section: Introductionmentioning
confidence: 99%